Recent advantages of colloidal photonic crystals and their applications for luminescence enhancement. (June 2019) - Li, M.; Lai, X.; Li, C.; Song, Y.
Abstract: Control of spontaneous emission is crucial to quantum optics and optical devices. It is essential for diverse applications ranging from miniature lasers, light-emitting diodes, and quantum information to solar energy harvesting. Photonic crystals (PCs) have the capacity to optimize the emission properties of active materials which provide an efficient strategy to construct highly efficient lighting devices, low-threshold lasers, sensitive fluorescent sensors, and so on. Colloidal photonic crystals (CPCs) are close-packed ordered arrays self-assembled from monodispersed colloid spheres. The self-assembled CPCs have great advantages of low cost, flexibility, and easy processability which show great potential for create captivating and diverse photonic structures for new photonic materials and devices. Here, we summarize the recent advantages of the CPC fabrication and its superior capacity for luminescence enhancement. Based on the current research studies, we offer a perspective on how to make full use of the advantages of the CPC-enhanced luminescence to construct novel, efficient, eco-friendly, and low-cost optical devices such as optical sensors, lasers, and displays. Graphical abstract: Image 1 Highlights: Photonic crystals (PCs) show great potential for creating captivating and diverse photonic structures for new photonic materials and devices. PCs made from self-assembled colloidal particles (CPCs) have great advantages of low cost, flexibility, and easy processability. The recent advantages of the colloidal PC fabrication and its superior capacity for luminescence enhancement are summarized. Some inspiration to the community and a clear vision for the future PC-structured devices are provided.